Environmental returns to education: an application to waste management in quilmes county of Argentine - Saidon, Mariana (2013)
This paper presents estimations about the nascent field of environmental returns to education. It focuses on household solid waste and analyzes the case of the urban district of Quilmes, Argentina. Models were estimated using Two-Stage Probit Least Squares. The results suggest that education would appear to be relevant to explaining knowledge in terms of understanding environmental implications of waste management once agents have been provided with some background information. However, a higher level of education was not significant when explaining the availability of information about the subject. On the other hand, there is evidence of a significant incidence of knowledge -both in terms of availability of information, and understanding- about the likelihood that the public is willing to cooperate (voluntarily) in a recycling program. Therefore, there are positive and significant environmental returns to education through understanding regarding the probability that a person is willing to separate his or her own waste once the agent acquires baseline information about the topic.